-2x+23=2x+11

Simple and best practice solution for -2x+23=2x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+23=2x+11 equation:


Simplifying
-2x + 23 = 2x + 11

Reorder the terms:
23 + -2x = 2x + 11

Reorder the terms:
23 + -2x = 11 + 2x

Solving
23 + -2x = 11 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
23 + -2x + -2x = 11 + 2x + -2x

Combine like terms: -2x + -2x = -4x
23 + -4x = 11 + 2x + -2x

Combine like terms: 2x + -2x = 0
23 + -4x = 11 + 0
23 + -4x = 11

Add '-23' to each side of the equation.
23 + -23 + -4x = 11 + -23

Combine like terms: 23 + -23 = 0
0 + -4x = 11 + -23
-4x = 11 + -23

Combine like terms: 11 + -23 = -12
-4x = -12

Divide each side by '-4'.
x = 3

Simplifying
x = 3

See similar equations:

| 2x+3x-1+2x+3x-1= | | 4(k-6)=2(k+2) | | 5(3m-2)-(m-3)=13-4(-4m+5) | | 10-(2z-6)=4-3z | | 6a+3=2a-13 | | 4.4y=-88 | | -6x+56=-9-31 | | 2(-3)=76 | | 9.2y=-88 | | 0.71*x=3 | | 2n+5=(n-2)-n | | 8=2x-3y | | 3(3v-2)=4(2v+2) | | 2X+1-4=-2X-34 | | 4z/10+7=8 | | 12x=2x+10x+1 | | 3m-8m=110 | | x/9+3=6 | | 9(1.082x+1)=15 | | z/7+3=6 | | 15x^2-47x-10=0 | | 137-(6x+5)=6(x+9)+x | | 2/3x–6=9 | | 5x-4=x+3*2 | | 5[2-g]=0 | | 14=3m+5 | | 5+6=4+Y | | 10[1-2y]=-5[2y-1] | | -3sin(t)+2cos(t)=0 | | 3(3+2x)-4x=59-3x | | 15z-2=(2z+3) | | 3x-(12x-x)=5+2(x-1)-1 |

Equations solver categories